2020
DOI: 10.1089/thy.2019.0175
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Receptor β Inhibits Self-Renewal Capacity of Breast Cancer Stem Cells

Abstract: Background: A subpopulation of cancer stem cells (CSCs) with capacity for self-renewal is believed to drive initiation, progression, and relapse of breast tumors. Methods: Since the thyroid hormone receptor b (TRb) appears to suppress breast tumor growth and metastasis, we have analyzed the possibility that TRb could affect the CSC population using MCF-7 cells grown under adherent conditions or as mammospheres, as well as inoculation into immunodeficient mice. Results: Treatment of TRb-expressing MCF-7 cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 56 publications
3
31
0
Order By: Relevance
“…Considering the subcellular THRβ1 localization seems to be essential for further analysis of its impact on patient outcome. A recent in vitro study suggested a novel role of THRβ, namely THRβ1, in the biology of cancer stem cells that could explain its action as a tumor suppressor in BC [38]. In our study, both nuclear and cytoplasmic THRβ1 strongly correlate positively with CD133 and N-cadherin, without any differential effect according to their subcellular location.…”
Section: Discussionsupporting
confidence: 57%
“…Considering the subcellular THRβ1 localization seems to be essential for further analysis of its impact on patient outcome. A recent in vitro study suggested a novel role of THRβ, namely THRβ1, in the biology of cancer stem cells that could explain its action as a tumor suppressor in BC [38]. In our study, both nuclear and cytoplasmic THRβ1 strongly correlate positively with CD133 and N-cadherin, without any differential effect according to their subcellular location.…”
Section: Discussionsupporting
confidence: 57%
“…TRβ has shown to be a potent tumor suppressor in several types of cancer including breast and thyroid cancer (15,16,35,36). However, there are only a few tumor suppressive mechanisms delineated in the literature, which include TRβ-mediated JAK1/STAT1 activation and binding to p85⍺ (15,20,35).…”
Section: Discussionmentioning
confidence: 99%
“…These TRβ-expressing tumors showed evidence of reduced PI3K-Akt signaling and less blood vessel formation compared to tumors without TRβ expression. Most recently, TRβ restoration has been shown to suppress growth and migration in colorectal cancer cells [17], and block cancer stem cell out growth in luminal A breast cancer cell lines [18]. Our lab demonstrated that restoration of TRβ in anaplastic thyroid cancer cells re-programs the transcriptome, promotes apoptosis, and suppresses many of their aggressive phenotypic traits [19].…”
Section: Trβ Satisfies the Criteria For A Tumor Suppressormentioning
confidence: 72%
“…There was also a decrease in vascular endothelial growth factor (VEGF) levels which stimulates endothelial cells to promote angiogenesis by way of the PI3K pathway, further implicating a broad-spectrum tumor suppressive role of TRβ. Additionally, TRβ transduction resulted in reduced autocrine signaling in an MCF-7 model [18]. TRβ-T3 decreased expression of vascular endothelial growth factor receptor 9 (FGFR9) and cognate ligands FGF3 and FGF4, while blunting estrogen-mediated induction of FGF9.…”
Section: Trβ Attenuates the Pi3k-akt Signaling Pathway Via Genomic And Nongenomic Mechanismsmentioning
confidence: 99%